Changes in potassium sorption and pH buffering capacity of tropical acid soils following application of charcoal and sago bark ash - Paramisparam, Puvan; Ahmed, Osumanu Haruna; Ch’ng, Huck Ywih; Omar, Latifah; Johan, Prisca Divra; Hamidi, Nur Hidayah; Musah, Adiza Alhassan (Malaysian Society of Soil Science, 2023)
Ultisols and Oxisols are the two dominant soils in the tropics. These soils are mostly infertile and have low cation exchange capacity because of their low pH (4 to 5). They are composed of kaolinite and sesquioxides which are prone to potassium (K) leaching. To make these soils arable, liming and fertilization are required. Nevertheless, this conventional practice alone does not mitigate K availability in such soils because of their low pH buffering capacity and low K adsorption capacity. The alkalinity of sago (Metroxylon sagu) bark ash and charcoal and the deprotonation of charcoals functional groups by the carbonates and oxides of sago bark ash have potential benefits. Due to these characteristics of sago bark ash and charcoal, they could be utilized to improve soil pH buffering capacity and K adsorption capacity to prevent the leaching of K and the pollution of water bodies. Moreover, the use of charcoal and sago bark ash to amend soils is a good way of utilizing agro-wastes sustainably. Thus, the objective of this study was to determine the effects of amending tropical acid soils with charcoal and sago bark on K sorption and pH buffering capacity. The treatments evaluated were: (i) 300 g soil only, (ii) 250 g charcoal only, (iii) 250 g sago bark ash only, (iv) 300 g soil + 15.42 g charcoal, (v) 300 g soil + 7.71 g sago bark ash, and (vi) 300 g soil + 15.42 g charcoal + 7.71 g sago bark ash. Langmuir bonding energy constant (KL), Maximum K buffering capacity (MBC), and maximum adsorption capacity (qmax) of the soil with charcoal and sago bark ash were higher than that of soil alone. However, desorption of K was not significantly affected after application of the amendments. On the other hand, the combined use of charcoal and sago bark ash improved the soils pH buffering capacity in comparison to the untreated soil because of the inherently high CEC and alkalinity of these amendments. Therefore, this intervention could contribute to improving K fertilizer use and prevent environmental pollution and economical loss to farmers.